Mst4, a novel cardiac STRIPAK complex-associated kinase, regulates cardiomyocyte growth and survival and is upregulated in human cardiomyopathy - Eden, Matthias; Leye, Marius; Hahn, Justus; Heilein, Emanuel; Luzarowski, Marcin; Völschow, Bill; Tannert, Christin; Sossalla, Samuel; Lucena-Porcel, Carlota; Frank, Derk; Frey, Norbert (The journal of biological chemistry, 2024)
Myocardial failure is associated with adverse remodeling, including loss of cardiomyocytes, hypertrophy, and alterations in cell-cell contacts. Striatin-interacting phosphatase and kinase (STRIPAK) complexes and their mammalian STE20-like kinase 4 (Mst4) have been linked to development of different diseases. The role and targets of Mst4 in cardiomyocytes have not been investigated yet. Multitissue immunoblot experiments show highly enriched Mst4 expression in rodent hearts. Analyses of human biopsy samples from patients suffering from dilated cardiomyopathy revealed that Mst4 is upregulated (5- to 8-fold p < 0.001) compared with nonfailing controls. Increased abundance of Mst4 could also be detected in mouse models of cardiomyopathy. We confirmed that Mst4 interacts with STRIPAK components in neonatal rat ventricular cardiomyocytes, indicating that STRIPAK is present in the heart. Immunofluorescence stainings and molecular interaction studies revealed that Mst4 is localized to the intercalated disc and interacts with several intercalated disc proteins. Overexpression of Mst4 in cardiomyocytes results in hypertrophy compared with controls. In adult rat cardiomyocytes, Mst4 overexpression increases cellular and sarcomeric fractional shortening (p < 0.05), indicating enhanced contractility. Overexpression of Mst4 also inhibits apoptosis shown by reduction of cleaved caspase3 (-69%, p < 0.0001), caspase7 (-80%, p < 0.0001), and cleaved Parp1 (-27%, p < 0.001). To elucidate potential Mst4 targets, we performed phosphoproteomics analyses in neonatal rat cardiomyocytes after Mst4 overexpression and inhibition. The results revealed target candidates of Mst4 at the intercalated disc. We identified Mst4 as a novel cardiac kinase that is upregulated in cardiomyopathy-regulating cardiomyocyte growth and survival.
Gesehen am 03.07.2025